Helminth's assemblage of a small frog in the Brazilian semiarid: parasite-host-environment relationships - Soares, Pamella B. C.; Passos, Daniel C.; Anjos, Luciano A. dos [UNESP]; Wachlevski, Milena (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2022)
Parasite infections may contingency different aspects of the hosts' lives, and are usually expected to directly or indirectly compromise host reproduction. However, although amphibians have historically been study models in parasite ecology, the effects of parasitism on amphibians' reproduction remain unknown. Thus, we investigated how the parasite load varies as a function of climatic seasonality (rainy and dry season) and intrinsic host characteristics (size and sex), as well as the relationship between parasite load and reproductive investment in males and females of a small frog (Pseudopaludicola pocoto Magalhaes, Loebmann, Kokubum, Haddad & Garda, 2014) in the Brazilian semiarid region. The parasitological parameters of the studied population were not influenced by the season of the year or by the hosts' body size, but females of P. pocoto had a higher prevalence and intensity of infection than males. The number of oocytes and the volume of the testes were not related to the parasite load, revealing that the parasitism did not negatively impact the gonadal investment in P. pocoto. Our findings suggest that short-lived species, such as the tiny Pseudopaludicola species, have a high reproductive investment independent of their parasitic interactions. In addition, this should be true mainly in those species that live in seasonally dry environments, such as P. pocoto, in which reproduction is even more constrained by the shortened and unpredictable rainy period.
Keywords: Amphibia; Pseudopaludicola; Seasonality; Reproductive allocation; Nematoda